2017
DOI: 10.4103/1008-682x.189207
|View full text |Cite
|
Sign up to set email alerts
|

Dog sperm head morphometry: its diversity and evolution

Abstract: Dogs have been under strong artificial selection as a consequence of their relationship with man. Differences between breeds are evident that could be reflected in seminal characteristics. The present study was to evaluate differences in sperm head morphometry between seven well-defined breeds of dog: the British Bulldog, Chihuahua, German Shepherd, Labrador Retriever, Spanish Mastiff, Staffordshire Terrier, and Valencian Rat Hunting dog. Semen samples were obtained by masturbation and smears stained with Diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 36 publications
(44 reference statements)
3
30
0
3
Order By: Relevance
“…In particular, associations between sperm head dimensions and swimming parameters have been recorded in birds and mammals (Humphries, Evans, & Simmons, ; Lüpold et al, ; Malo et al, ). In a previous study, we examined dimensions of the sperm head in different dog breeds (Soler et al, ) and a preliminary comparison between them and those of the present study suggest a trend for a positive link with motility, spermatozoa with bigger heads exhibiting higher velocities. This apparent association requires further examination on a larger number of animals and breeds.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In particular, associations between sperm head dimensions and swimming parameters have been recorded in birds and mammals (Humphries, Evans, & Simmons, ; Lüpold et al, ; Malo et al, ). In a previous study, we examined dimensions of the sperm head in different dog breeds (Soler et al, ) and a preliminary comparison between them and those of the present study suggest a trend for a positive link with motility, spermatozoa with bigger heads exhibiting higher velocities. This apparent association requires further examination on a larger number of animals and breeds.…”
Section: Discussionsupporting
confidence: 54%
“…Manual stimulation was used to collect semen samples into sterile sample cups (Soler et al, ). Since a high sperm concentration can have a confounding effect on sperm velocity and linearity (Günzel‐Apel, Günther, Terhaer, & Bader, ; Rijsselaere, Van Soom, Maes, & de Kruif, ), all samples with >50 × 10 6 sperm/ml were diluted with CaniPlus Chill ® sperm extender (Minitub Ibérica S.L., Tarragona Spain) before motility analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that mammalian sperm morphometric differences can have an evolutionary significance11 in different species’ diversity (dog,12 rodents,1314 South America camelids15). Similar works could also be done on the Felidae family.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, multivariate analysis has been introduced for the simultaneous consideration of all the parameters, including their relationships 24. During recent decades, new efforts have been made to define the best analytical approaches by using subpopulation analysis25 and morphological sperm subpopulation structure, based on morphometric data, which has been observed in a great variety of species: dogs,2627 boars,2829 bulls,3031 foxes,32 humans,3334 llamas,15 marmosets,35 pumas,36 rabbits,37 rams,383940 red deer,41 and stallions 42…”
Section: Introductionmentioning
confidence: 99%